A comparative study on the in vitro and in vivo antitumor efficacy of icaritin and hydrous icaritin nanorods. (1st January 2020) - Li, Haowen; Li, Yijing; Ao, Hui; Fu, Jingxin; Guo, Yifei; Han, Meihua; Yan, Xueying; Chen, Xi; Wang, Xiangtao
Abstract: Icaritin (ICT) and hydrous icaritin (HICT) are two similar flavonoids compounds isolated from Epimedium Genus. This is the first comparative study on their in vitro and in vivo antitumor effects. Nanorods (NRs) were prepared for ICT and HICT by anti-solvent precipitation method using D-alpha tocopherol acid polyethylene glycol succinate (TPGS) as a stabilizer. The prepared ICT-NRs and HICT-NRs had similar diameter (155.5 nm and 201.7 nm), high drug loading content (43.30 ± 0.22% and 41.08 ± 0.19%), excellent stability and a similar sustaining drug release manner. Nanorods improved the in vitro toxicity against 4 different cancer cells in contrast to free ICT or free HICT; however, no significant difference was observed in this regard between ICT-NRs and HICT NRs. In the in vivo study on the anticancer efficacy on MCF-7 and PLC/PRE/5 tumor-bearing mice model, HICR-NRs displayed certain advantage over ICT NRs with higher tumor inhibition rate.